c - Ekins, Paul; Gupta, Joyeeta, 1964-; Boileau, Pierre (Cambridge University Press, 2019)
Published to coincide with the Fourth United Nations Environmental Assembly, the Summary for Policymakers of the sixth Global Environment Outlook provides an evidence-based source of environmental information to help policymakers in government, local authorities and businesses achieve the UN's Sustainable Development Goals. Since the first edition in 1997, there have been many examples of environmental improvement, especially where problems have been well identified, manageable, and where regulatory and technological solutions have been readily available. Nevertheless, the overall condition of the global environment has deteriorated and urgent action, involving ambitious and effective policies, is necessary to arrest and reverse this situation. This Summary for Policymakers answers key policy questions by assessing the drivers of environmental change, the scale and effectiveness of policy responses, potential pathways for achieving sustainability goals in an increasingly complex world, and the data and information that can support the decision-making process. Also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 21 Jun 2019).
Keywords: Environmental policy -- International cooperation; Environmental protection -- International cooperation; Global environmental change